Inequality of Opportunity and Income Redistribution - Marcel Preuss; Germán Reyes; Jason Somerville; Joy Wu (ZBW - Leibniz Information Centre for Economics, 2022)
This paper examines how people redistribute income when there is uncertainty about the role luck plays in determining opportunities and outcomes. We introduce a portable experimental method that generates exogenous variation in the probability that real workers' earnings are due to luck, while varying whether luck interacts with effort in the earning process. Then, we elicit redistribution decisions from a U.S.-nationally representative sample who observe worker outcomes and whether luck magnified workers' effort ("lucky opportunities") or determined workers' income directly ("lucky outcomes"). We find that participants redistribute less and are less reactive to changes in the importance of luck in environments with lucky opportunities. We show that individuals rely on a simple heuristic when assessing the impact of unequal opportunities, which leads them to underappreciate the extent to which small differences in opportunities can have a large impact on outcomes. Our findings have implications for models that seek to understand and predict attitudes toward redistribution, while helping to explain the gap between lab evidence on preferences for redistribution and real-world inequality trends.
Keywords: C91; D63; 330